AN OPTIMIZED DNA ISOLATION PROTOCOL ENABLES AN INSIGHT INTO MOLECULAR GENETIC BACKGROUND OF ENDEMIC Moltkia petraea (Tratt.) Griseb. FROM BOSNIA AND HERZEGOVINA - Jasna Hanjalić; Semir Dorić; Lejla Lasić; Belma Kalamujić Stroil; Selma Hasičić; Naris Pojskić (Genetics & Applications, 2017)
The Dinaric endemic plant species Moltkia petraea (Tratt.) Griseb. is often called a "living fossil" of ancient Tertiary flora, with great importance for Bosnia and Herzegovina’s biodiversity. Considering its narrow and limited distribution range, insufficient data on the molecular background of this species is given so far. Due to the presence of various secondary metabolites that interfere with the DNA, isolation of nucleic acids from plant cells is known to be challenging. Even in closely related species it is necessary to optimize DNA isolation protocol in order to obtain high quality PCR amplifiable DNA. We collected 91 samples from five populations in Herzegovina. Doyle and Doyle (1987) CTAB protocol was modified by adding vitamin C (ascorbic acid) to the cell lysis buffer to improve DNA yield and quality. trnL(UAA) intron and nrDNA (ITS1, ITS2) molecular markers were applied to demonstrate amplifiability of isolated DNA and elucidate the intra- and interpopulation genetic diversity. Our results suggest a successful PCR amplification for 81% of the analyzed samples. PCR-RFLP analysis of trnL(UAA) revealed that all individuals in five populations have the same haplotype based on the obtained enzymatic profile for three enzymes (TaqI, HinfI, HindII). Alignment and comparison of ITS sequences didn’t reveal any hypervariable portion that could be informative in elucidating the genetic diversity of M. petraea populations. Further studies with additional application of microsatellite loci, RAPD and AFLP methods are necessary in an attempt to get insights into the genetic diversity of M. petraea.